PEMANFAATAN KULIT DURIAN UNTUK MENGHASILKAN BAHAN BAKAR ALTERNATIF MELALUI PROSES FAST PYROLISIS - Muhammad Zanu Nur Arsyad Arsyad; Rany Puspita Dewi; Nur Hayati (POLITALA PRESS, 2025)
Durian skin waste has not been utilized properly so in the end it just piles up in the trash, so a study is needed to reduce the amount of durian skin waste that is not utilized properly. Pyrolysis is a heating process without oxygen. This study aimed to determine the amount of bio-oil, viscosity value, density value, and calorific value of the durian skin waste tested. Temperatures of 350 ℃, 400 ℃, and 450 ℃ are variations in this study. The study's results using the fast pyrolysis process were 120 ml, 130 ml, and 150 ml. The resulting viscosity values ​​are 5.4 mm²/s, 5.2 mm²/s, and 4.6 mm²/s, the resulting density values ​​are 725.5 kg/m³, 727.7 kg/m³, and 743.3 kg/m³. The resulting calorific values ​​are 14.6 MJ/kg, 17.1 MJ/kg, and 18.5 MJ/kg.